Initiating opportunistic breast cancer screening program for asymptomatic self-referring women in Iraq - Mustafa, Abdullateef A.; Hasan, Nada A.S.; Khalel, Enam A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Breast cancer is the most frequently diagnosed cancer in women worldwide and organized national mammographic screening has been adopted as gold standard for breast cancer early detection in most developed countries in the world.Objectives: to evaluate and emphasize the performance of the initiative opportunistic breast cancer screening program in Iraq and to determine the incident malignancy rate of breast cancer among asymptomatic self-referring women aged 40 years or older via digital mammography by mean of the breast imaging reporting and data system (BI-RADS©).Patients and methods: this retrospective study included a total of 809 asymptomatic self-referring women over age 40 years, mostly consisted of employees of the different Iraqi ministries who attended the national center of early detection of cancer in Medical City Complex at Baghdad for screening purpose during the period from September 2012- October 2013 by using digital mammography. Ultrasound examination performed as complementary study in particular cases and all cases are graded according BIRADS lexicon. BIRADS category 4 and 5 were followed by cytopathological analysis.Results: 809 asymptomatic self-referring women were included in this initiative screening program for early detection of breast cancer at the main breast care referral center in Baghdad. The mean age at presentation was 49 years (range 40–76 years). The current study found that overall incident malignancy rate among total sample of the study was 1.11% whilst individual malignancy rate per BI-RADS category was 11.1% for BI-RADS 4 lesions and 80% for BI-RADS 5 lesions.Conclusion: introduction of individual opportunistic screening program of breast cancer has led to a significant increase in early detection rate of breast cancer and enhance the health awareness for breast cancer screening among asymptomatic women.